KOMUNIKASI LINTAS BUDAYA ANTARA PENGLINGSIR PURI KANGINAN BULELENG DENGAN UMAT MUSLIM DALAM PRAKTIK MENYAMA BRAYA DI KELURAHAN KAMPUNG SINGARAJA KABUPATEN BULELENG PROVINSI BALI - Kusuma Negara, Eka Prasetya; Yuliani, Ni Made; Suwantana, I Gede (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
This study examines cross-cultural communication between Penglingsir Puri Kanginan Buleleng and Muslims community in Kampung Singaraja Subdistrict, Bali. The Muslims community in this area are descendants of the Blambangan Islamic Warriors, followers of the King of Buleleng, I Gusti Anglurah Panji Sakti. The Islamic Warriors were granted land by the King of Buleleng in 1711. Despite their different religious and cultural backgrounds, communication between the two groups has been intense, resulting in the practice of "menyama braya". This study focuses on patterns of cross-cultural communication, barriers to communication, and the implications of these communication practices. A qualitative method is used, employing the theories of interaction adaptation, accommodation, and negotiation to analyze the data. The results show that cross-cultural communication has produced cultural acculturation and the practice of "menyama braya" such as the bancakan tradition and involvement in religious ceremonies. However, communication is also hampered by barriers such as cultural differences, motivations, language, and stereotypes. Despite these challenges, communication is generally good. The younger generation is expected to take on a role in addressing these communication barriers so that the practice of "menyama braya" can continue into the future.